Clinical Assessment of a Local Application of Kasisadi Ghrita in Parikartika (Fissure-in-ano) - Snehal Kukade; Mamata Mate; Komal Kedar; Seema Thakre; Shailesh Nagpure (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Parikartika is charecterised by sharp cutting pain in anal region. In Parikartika Teevrashoola,bleeding is observed, equally extreme pain& slimy blood discharge are seen in Fissure-in-anoObjective: To test the efficacy of thelocal application of Kasisadi Ghruta in managingMethods: Classical signs and symptoms ofParikartika (fissure inAno) Age groups of 20 to 60 years havebeen recruited for the researchThe trial group obtained treatment with Kasisadi Ghruta local application for28 days, twice a day.Results: Average relief observed was observed 62.5% for most symptoms Shothahara, Vedanasthapana andRopana are in Kasisadi Ghruta. Properties because of which it helps in healing the ano fissureConclusion: Local Kasisadi Ghruta The programme has better results in the Fissure in ano.